Real-time 3D scans of cardiac surgery using a single optical-see-through head-mounted display in a mobile setup - Dewitz, Bastian; Bibo, Roman; Moazemi, Sobhan; Kalkhoff, Sebastian; Recker, Stephan; Liebrecht, Artur; Lichtenberg, Artur; Geiger, Christian; Steinicke, Frank; Aubin, Hug; Schmid, Falko (Frontiers in Virtual Reality, 2022)
Microsoft HoloLens 2 (HL2) is often found in research and products as a cutting-edge device in Mixed Reality medical applications. One application is surgical telementoring, that allows a remote expert to support surgeries in real-time from afar. However, in this field of research two problems are encountered: First, many systems rely on additional sensors to record the surgery in 3D which makes the deployment cumbersome. Second, clinical testing under real-world surgery conditions is only performed in a small number of research works. In this article, we present a standalone system that allows the capturing of 3D recordings of open cardiac surgeries under clinical conditions using only the existing sensors of HL2. We show difficulties that arose during development, especially related to the optical system of the HL2, and present how they can be solved. The system has successfully been used to record surgeries from the surgeons point of view and to reconstruct a 3D view in real-time which can be streamed over network to a remote expert. In a study, we present a recording of a captured surgery under real-world clinical conditions to expert surgeons which estimate the quality of the recordings and their overall applicability for diagnosis and support. The study shows benefits from a 3D reconstruction compared to video-only transmission regarding perceived quality and feeling of immersion.